Inovasi Layanan Digital Berbasis Syariah Sebagai Strategi Peningkatan Daya Saing Perbankan Syariah Indonesia - Nur Sa'idaturrohmah; Anna Putri Syafitri (Al-Musthofa: Journal of Sharia Economics, 2026)
The development of digital technology has brought major changes to the banking industry, including sharia banking in Indonesia. Bank Syariah Indonesia (BSI) as the largest sharia financial institution in Indonesia is required to continue to innovate digital products to increase competitiveness amidst increasingly fierce competition in the financial industry. This research aims to analyze digital product innovation implemented by Bank Syariah Indonesia and its impact on increasing the company's competitiveness. The research method used is a literature study by reviewing various scientific literature, journals, books and reports related to the digitalization of sharia banking. The research results show that digital innovations such as sharia mobile banking, online account opening, QRIS, digital payment services, and halal ecosystem integration are able to increase service efficiency, customer satisfaction, and expand BSI's market share. Apart from that, digital transformation also strengthens BSI's competitive position in facing the development of fintech and digital-based conventional banks. Thus, digital product innovation is an important strategy in increasing the competitiveness and sustainability of Bank Syariah Indonesia